Perancangan Sistem Monitoring Barang Logistik Berbasis IoT - Agung Syaputra; Tata Sutabri (Switch : Jurnal Sains dan Teknologi Informasi, 2024)
An Internet of Things (IoT)-based logistics monitoring system is an innovation designed to enhance efficiency, transparency, and speed in supply chain management. The implementation of IoT in logistics provides an ideal solution for real-time monitoring of goods, which was previously difficult with conventional methods. This system integrates IoT sensors such as GPS for location tracking, along with temperature and humidity sensors to monitor goods requiring special attention, such as food and pharmaceuticals. By automating processes through IoT technology, goods distribution becomes faster, reducing reliance on manual controls, speeding up decision-making, and minimising human error. This system enables companies to monitor the condition and location of goods in real-time, offering high visibility into the logistics status. With comprehensive monitoring, companies can proactively address issues and ensure goods remain in optimal condition throughout the shipping process. An IoT-based logistics monitoring system has the potential to enhance a company’s competitiveness through efficiency and accuracy in supply chain management. When effectively implemented, IoT technology can not only improve service quality and customer satisfaction but also strengthen a company’s position in an increasingly competitive market.